Need Analysis of Japanese Grammar Learning Media - Ramadhan, K; Setiana, S M (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
This study aims to analyze the needs of grammar learning media in Kiso Nihongo Course. This study used a quantitative descriptive method using a questionnaire research technique. The questionnaire used is a closed-type questionnaire with several statements distributed via Google Forms. The respondent for this study was 25 students of the Japanese Department Faculty of Humanities Universitas Komputer Indonesia for the academic year 2022/2023. The results showed that learning Japanese grammar which is currently taking place in the Japanese Department at the Universitas Komputer Indonesia is going well. However, students feel that Japanese grammar learning media is needed to help the Japanese grammar learning process become better. Most of the students said that Japanese grammar learning media was needed to help them understand the material in the Kiso Nihongo Course. Learning media that are believed to be effective in helping the Japanese grammar learning process are video tutorials type. To improve the quality of learning Japanese grammar, the use of various media is needed. By conducting this study, the expected outcome is learning media for Japanese grammar that suit the needs of students can be created to make the learning process at the Kiso Nihongo Course better.